Designing Web Sites Location Tour in Yogyakarta Using Macromedia Flash MX - Anom Tri Haryanto (Jurnal Sistem Informasi, 2005)
Website is a means to convey information, whether it be updated or fixed. other than as a means of information, other functions of the website as well as media to perform the commercialization or e-commerce, what should be offered to visitors, this is usually done by many companies to advertise their website pruduknya through the site. The web address used on this site is http://www.geocities.com/bdy_darmaxx/, 09 August 2004 at 07.00 pm.Web site designed as a tourist information service delivery and provision of travel brochures for anyone who wants to visit the tourist areas in Central Java, by opening this website we can find the histories of the temples of Prambanan and Borobudur temple Parangtritis beach. But in making this site is not intended for e-commerce services due only to meet these scientific writing.